Exercise testing after beta-blockade: improved specificity and predictive value in detecting coronary heart disease. Issue 3 (March 1980) - Marcomichelakis, J; Donaldson, R; Green, J; Joseph, S; Kelly, H B; Taggart, P; Somerville, W
Abstract : The value of exercise testing in detecting myocardial ischaemia resulting from coronary atheroma remains controversial. In order to increase the reliability of exercise testing, all its components (asymptomatic, haemodynamic, and electrocardiographic) have been scrutinised. In this study, concerned only with the electrocardiographic response to exercise, the incorporation of beta-blockade into the standard exercise procedure has improved specificity and predictive value without affecting sensitivity. Fifty patients with anginal pain and 50 asymptomatic subjects with an abnormal electrocardiogram were investigated by exercise testing before and after beta-blockade (oxprenolol). All subjects had coronary arteriograms and left ventriculograms, and the results of exercise testing were related to the presence or absence of obstructive coronary artery disease. Possible causes of false positive exercise tests were eliminated by echocardiography. Though beta-blockade was unreliable in distinguishing ischaemic from non-ischaemic resting electrocardiograms, it eliminated all the false positive electrocardiographic responses to exercise in both groups and did not abolish any of the true positive electrocardiographic responses. Thus, specificity and predictive value were improved without reduction in sensitivity. This technique may not necessarily be applicable to other groups of patients or to a random population, but the results of this study suggest it will be a useful additional routine procedure in the investigation of coronary heart disease.